THE EFFECTIVENESS OF PRE-READING STRATEGIES TO IMPROVE STUDETNS’ READING COMPREHENSION AT SMP NEGERI 16 BULUKUMBA - Putri. A, Nurfaika; Natsir, Ratu Yulianti; Ariana (FKIP Unismuh Makassar, 2024)
The objective of this study was to find out if the use of pre-reading strategies was capable of increased students’ learning result of 9th grade students’ at SMP Negeri 16 Bulukumba. This research was divided class into 2 classes that refer to the control class and experimental class. The researcher data were collected through pre-test and post-test given to students and analyzing data using SPSS. The test gives to students in the form of pre-test as the beginning and post-test as the end of learning after given the treatment. The subject of the study was the students of grade 9th at SMP Negeri 16 Bulukumba as the research location and taking samples with a total population of 89 9th grade students while the sample used was 60 students, 30 students in control class and 30 students in experimental class. The result of this study showed that the pre-reading strategies could improve students’ learning result in reading comprehension where the pre-test of generic tructure is 78 and post-test is 80 for control class, while for experimental class the pre-test is 66.33 and 81 for post-test. For vocabulary results of control class, the pre-test is 77.66 and 92.33 for post-test (noun) 52.33 pre-test and 64.83 post-test (verb). In experimental class the pre-test is 59.66 and 91 for post-test (noun), 47.66 pre-test and 67.7 post-test (verb). in the end the value conclude of reading comprehension students’ in control class are 69.33 for pretest, 79.05 for postest. While in experiment class 57.88 for pretest and 79.9 for posttest. The students’ learning result that have been contained in this study showed improvement. On the initial ability of students’ pre-test the result obtained by students’ the average score of the class is less than post-test result, both in control class and experimental class, the result obtained by students’ in both of control and experimental class an increase in students’ learning result in reading comprehension. And it is proven again from the results of the analysis of the